Tribological enhancement of modified jatropha oil by activated carbon nanoparticle for metalworking fluid application - Talib, Norfazillah; Sabri, Ainaa Mardhiah; Zolkefli, Ariff Azizi; Kai, Sheng Tan; Kunar, Sandip (Malaysian Tribology Society (MYTRIBOS), 2022)
The excessively use of petroleum-based oil as a metalworking fluid is hazardous to the worker and cause a pollution to the environment. As a result, environmentally friendly oil has gradually replaced petroleum-based oil in the machining process. The goal of this study is to investigate the tribological enhancement of modified jatropha oil (MJO) by activated carbon nanoparticle (AC) ranging from 0.01 to 0.05 wt.% through the four-ball test and turning process. The results reveal that MJO with 0.025wt% AC nanoparticle has exceptional tribological performance in terms of friction and wear, resulting in extended tool life in terms of machining length (7000mm) and machining time (49 minutes). The addition of 0.025wt.% AC nanoparticle created a protective layer that facilitates rolling action at the sliding surfaces. As a result, MJO with 0.025wt% AC has excellent tribological properties, making it a viable alternative as an environmentally friendly metalworking fluid.